2019
DOI: 10.3389/fpsyt.2019.00096
|View full text |Cite
|
Sign up to set email alerts
|

Narrative Case Notes Have the Potential to Predict Seclusion 3 Days in Advance: A Mixed-Method Analysis

Abstract: Objectives: Current risk assessment tools can predict problematic behavior and the need for coercive measures, but only with a moderate level of accuracy. The aim of this study was to assess antecedents and triggers of seclusion. Methods: Narrative notes of health care professionals on psychiatric inpatients were analyzed daily starting 3 days prior to seclusion in the case group ( n = 26) and compared to a matched control group without seclusion ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…Retrospective case note studies are commonly used within medical research [ 29 , 30 ]. Within medical research, retrospective case note research has examined both physical [ 29 , 30 ] and psychiatric conditions [ 31 , 32 ]. In psychiatric care, case note research has been shown to predict seclusion [ 32 ], at-risk groups for PICU referral [ 33 ], and the need for multi-faceted diagnostic tools to ensure accuracy [ 34 ].…”
Section: Strengths and Limitations To The Study Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Retrospective case note studies are commonly used within medical research [ 29 , 30 ]. Within medical research, retrospective case note research has examined both physical [ 29 , 30 ] and psychiatric conditions [ 31 , 32 ]. In psychiatric care, case note research has been shown to predict seclusion [ 32 ], at-risk groups for PICU referral [ 33 ], and the need for multi-faceted diagnostic tools to ensure accuracy [ 34 ].…”
Section: Strengths and Limitations To The Study Designmentioning
confidence: 99%
“…Inter-rater reliability and how practitioners come to decisions is often limited to assumptions drawn by them. Clinical involvement for accuracy is reliant on clinical records, which allow for the capture of behaviour prior to diagnoses, that may not be captured in typical records, allowing the identification of meaningful predictors for diagnoses [ 32 , 40 ].…”
Section: Strengths and Limitations To The Study Designmentioning
confidence: 99%
“…Retrospective case note studies are commonly used within medical research (29,30). Within medical research, retrospective case note research has examined both physical (29,30) and psychiatric conditions (31,32). In psychiatric care, case note research has been shown to predict seclusion (32), at-risk groups for PICU referral (33), and the need for multi-faceted diagnostic tools to ensure accuracy (34).…”
Section: Strengths and Limitations To The Study Designmentioning
confidence: 99%
“…Furthermore, it seems that imposing restrictions on patients (i.e. treatment on a closed ward) may increase violent behavior (16,17). However, further research is needed (3,18).…”
Section: The Pros and Cons Of Closed Doors In Psychiatrymentioning
confidence: 99%